How Best to Motivate Lecturers for Better Service Delivery in Nigerian Universities - Ekundayo, H. T.; Ayodele, V. O. (Mediterranean Journal of Social Sciences, 2019)
The study examined how lecturers in Nigerian universities can be motivated towards better service delivery. The study also examined the level of motivation as well as job performance of the lecturers. The descriptive survey design was used for the study. The population consisted of lecturers and students of three government owned universities in Ondo and Ekiti States. The sample comprised of 220 lecturers and 500 students randomly selected from three institutions. Two self-designed instruments were used to collect the relevant data for the study. The data were analysed using the frequency counts, percentage scores and bar charts. The study revealed that the level of lecturers’ motivation and job performance was moderately high. The study further showed the various strategies that can enhance better service delivery by the university lecturers, if well implemented. They include: increasing pay package, creating opportunity for professional growth, promoting lecturers when due and providing safe and healthy environment for teaching-learning among others. Based on the findings, it was recommended that the government should give more attention to the teaching-learning environment which can help impact on the quality of outputs being turned out from the universities. It was again recommended that the various strategies suggested in this paper should be put in place by the university management in order to ensure better service delivery by the university lecturers.